Matemática discreta: médias e princípio das gavetas - Muniz Junior, Carlos Alberto (2016)
We present the main concepts of averages: Arithmetic, Geométrica, Harmonica and Quadratic and also the Dirichlet's Drawer Principle. We highlight as the main directions of this work, the application of these in various areas of mathematics and the ability to work with such content in high school. We also emphasize the main theorems approached, which are the Inequality of Medium and theorems Ramsey and Dirichlet that are nontrivial applications of the Drawer Principle.